2015
DOI: 10.1002/j.1839-4655.2015.tb00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Reoffending: a ten‐year retrospective cohort analysis

Abstract: Criminologists and other developmental researchers have long acknowledged the importance of both continuity and change in antisocial and criminal behaviour over the life-course. To the extent that young offenders having contact with the police will persist with offending into adulthood is an important social issue with significant implications for the ongoing development and implementation of early intervention and prevention programs. Using data from New South Wales, this paper tracks a cohort of 8,797 juveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Findings related to research question 2 demonstrate a statistically significant increase in the effectiveness of diversion on reoffending from the 1995 to the 1998 cohort, but no difference between the 1995 and 2002 cohort. Overall, police-led diversion remained strongly associated with reduced risk of reoffending, and this is consistent with previous research on the impact of police-led diversion on youth offending (Dennison et al, 2006;Payne & Weatherburn, 2015;Wilson & Hoge, 2013). Findings also indicate a higher overall risk of reoffending in the 2002 cohort compared to the 1995 cohort, indicating reduced time between the first and second offending incidents in the most recent cohort.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Findings related to research question 2 demonstrate a statistically significant increase in the effectiveness of diversion on reoffending from the 1995 to the 1998 cohort, but no difference between the 1995 and 2002 cohort. Overall, police-led diversion remained strongly associated with reduced risk of reoffending, and this is consistent with previous research on the impact of police-led diversion on youth offending (Dennison et al, 2006;Payne & Weatherburn, 2015;Wilson & Hoge, 2013). Findings also indicate a higher overall risk of reoffending in the 2002 cohort compared to the 1995 cohort, indicating reduced time between the first and second offending incidents in the most recent cohort.…”
Section: Discussionsupporting
confidence: 88%
“…Youth Justice Conferencing, a diversion program that focuses on engaging young people in a restorative justice process with their victims, has been found to have modest, positive effects by reducing recidivism among young people compared to traditional justice pathways (Sherman et al, 2015). Similarly, studies have found that young people who are cautioned display a longer time to re-offend and a reduced volume of offending overall (Payne & Weatherburn, 2015;Dennison et al, 2006;Shirley, 2017).…”
Section: Changes In Criminal Justice Diversionmentioning
confidence: 99%
“…Wales among 8,797 juvenile offenders aged 10-17 years showed that male delinquents recidivated significantly more than female delinquents over a 10-year follow up period (Payne & Weatherburn, 2015). Twenty-eight percent of 402 delinquents between ages 11-17 recidivated in the North Eastern US over a period of 12 months and the proportion of male recidivists (32%) was significantly higher than the proportion of female recidivists (22%) (Conrad et al, 2014).…”
Section: Introductionmentioning
confidence: 96%